Migration and servicification: Do immigrant employees spur firm exports of services?. (21st July 2019) - Hatzigeorgiou, Andreas; Lodefalk, Magnus
Abstract: Services play an increasingly important role in production, employment and international trade but are subject to substantially higher trade costs relative to manufactured goods. Knowledge of how these trade costs can be mitigated is important for facilitating trade of services. In this paper, we analyse the role of immigrant employees as facilitators of firm exports of services, a role that remains largely unexamined. We bridge the gap in existing research by drawing on new data for nearly 30, 000 Swedish firms during the period 1998–2007 within a heterogeneous firm framework. The results have important policy implications. As the multilateral approach to facilitating trade is challenged and more countries are imposing measures to restrict the cross‐country mobility of people, policymakers may need to find new ways to promote exports of services. Our results indicate that immigrant employees spur firms' export of services activities: hiring one additional foreign‐born worker can increase services exports by approximately 2.5 per cent, on average, with a stronger effect found for skilled and newly arrived immigrants. Therefore, policymakers could leverage the findings of this study to implement initiatives that utilise high‐skilled immigrants to promote services exports.